Impact of recycling on the mechanical properties of nickel-titanium alloy wires and the efficacy of their reuse after cold sterilization - Ankit Yadav; Poonam K Jayaprakash; Rajeshwar Singh; Meeta Dawer; Palash Modi; Bhumika Sehdev; Kiran K Ganji (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: This study aimed to assess the feasibility of reusing nickel-titanium (NiTi) alloy wires after 6 weeks of intraoral use by evaluating the changes in the load-deflection properties and surface characterization of these alloy wires after cold sterilization by immersion in 2% of acidic glutaraldehyde for 10 h. MATERIAL AND METHODS: Twenty wires each in three groups of G1-as-received wires (ARW), G2-unsterilized used wires, and G3-sterilized used wires (SUW) were tested by the three-point bending test and scanning electron microscopy (SEM). The data were subjected to statistics, one-way analysis of variance, and Bonferroni posthoc test for comparison. RESULTS: Recycling of NiTi wires produced statistically insignificant changes in both the loading and unloading properties of the wires. The forces needed to twist the used wires, that is, G2-(UUW) and G3-(SUW) were lower than G1-(ARW), suggesting lowering of the stiffness of the wires. Superelasticity is well-maintained by G2-(UUW) and G3-(SUW) although there is an insignificant lowering of the forces exerted by them during loading and unloading. SEM demonstrated no increase in the pitting of surfaces in both G2-(UUW) and G3-(SUW); multiple areas were seen to be more smoothened over G2-(UUW) and G3-(SUW) NiTi wires surfaces. CONCLUSION: The findings of this study support the reuse of NiTi wires after 6 weeks of use in oral conditions followed by cold sterilization by immersion in 2% acidic glutaraldehyde for 10 h.